IBRAHIM B. KHUJASH AND SPIRITUAL TIES BETWEEN THE VOLGA REGION AND DAGESTAN - Adygamov, Ramil' Kamilovic (History, Archeology and Ethnography of the Caucasus, 2023)
With the development of diverse, and especially spiritual ties between the republics of Tatarstan and Dagestan, the issue of studying the historical connection between them is becoming increasingly relevant. This problem is studied in the publications of Khabutdinov A.Yu., Bobrovnikov V.O., Navruzov A.R., Shikhaliev Sh.Sh., Safargaleev I.F., Malikov R.I., Kemper M. et al. Some of the research papers at Kazan Islamic University were dedicated to her. But the issue remains not fully investigated. This problem needs a more comprehensive and in-depth study, since it is known that there were spiritual, personal and commercial ties between the theologians of the two regions. A deeper study of it could also give an idea of the mutual influence of the ideas of the theologians of the two regions. This problem also requires the study of individual personalities, one of the most famous among them is Ibrahim Khujash. He and his relative were among the first Tatar imams of the XVIII – XIX centuries who were educated in Dagestan. He is mentioned in the works of S. Marjani, M. Ramzi and R. Fakhrutdin, and a number of Dagestani theologians. Thus, the purpose of this article is to study already known studies on this topic, to identify and analyze information about the life and work of Ibrahim Khujash, as well as an attempt to trace the connection between the influence of Dagestan education on the views and activities of the theologian. An analysis of the literature on this topic has shown that the problem hasn’t been solved and needs a deeper and more comprehensive study. The biography of Ibrahim Khujash in various sources is presented quite briefly. It follows from it that they, having been educated in Dagestan and some cities of the Ottoman Empire, returned to their homeland and performed the duties of an imam. His zealous attitude to the Sunnah, and harsh criticism of folk traditions, makes it possible to assume the influence of Dagestan education, in which the study of hadith played an important role.